Dynamic and incapsulating processes in the generation of the world demand - BIASCO, S. (PSL Quarterly Review, 2013)
The work argues that since the seventies the international economy has oscillated between two kinds of flow structures, one reflected in the upswing and the other in the downswing. In both cases, the international economy suffered, although in different ways, from the disappearance of some of the “safety valves” that had made it possible during the fifties and sixties for ex ante incongruities to be resolved without impeding the generation and transmission of output and income growth. Dealing with the stylised facts, the author brings out similarities in flow structures and in the corresponding adjustment problems recurring in the cycle. The author concentrates on relationships which have influenced the industrial part of the world, and examines them in a systemic approach covering the entire network of world connections. JEL: F44, E32